Does Candida and/or Staphylococcus play a role in nipple and breast pain in lactation? A cohort study in Melbourne, Australia. Issue 3 (9th March 2013) - Amir, Lisa H; Donath, Susan M; Garland, Suzanne M; Tabrizi, Sepehr N; Bennett, Catherine M; Cullinane, Meabh; Payne, Matthew S
Abstract : Objective: To investigate Candida species and Staphylococcus aureus and the development of 'nipple and breast thrush' among breastfeeding women. Design: Prospective longitudinal cohort study. Setting: Two hospitals in Melbourne, Australia (one public, one private) with follow-up in the community. Participants: 360 nulliparous women recruited at ≥36 weeks' gestation from November 2009 to June 2011. Participants were followed up six times: in hospital, at home weekly until 4 weeks postpartum and by telephone at 8 weeks. Main outcome measures: Case definition 'nipple and breast thrush': burning nipple pain and breast pain (not related to mastitis); detection of Candida spp (using culture and PCR) in the mother's vagina, nipple or breast milk or in the baby's mouth; detection of S aureus in the mother's nipple or breast milk. Results: Women with the case definition of nipple/breast thrush were more likely to have Candida spp in nipple/breast milk/baby oral samples (54%) compared to other women (36%, p=0.014). S aureus was common in nipple/breast milk/baby samples of women with these symptoms as well as women without these symptoms (82% vs 79%) (p=0.597). Time-to-event analysis examined predictors of nipple/breast thrush up to and including the time of data collection. Candida in nipple/breast milk/baby predicted incidence of the case definition (rate ratio (RR) 1.87 (95% CI 1.10 to 3.16, p=0.018). We do not have evidence that S aureus colonisation was a predictor of these symptoms (RR 1.53, 95% CI 0.88 to 2.64, p=0.13). Nipple damage was also a predictor of these symptoms, RR 2.30 (95% CI 1.19 to 4.43, p=0.012). In the multivariate model, with all three predictors, the RRs were very similar to the univariate RRs. This indicates that Candida and nipple damage are independent predictors of our case definition.